Personality Traits and Insomnia Symptoms in Shift Workers - Holzinger, Brigitte; Mayer, Lucille; Klösch, Gerhard (Frontiers in Psychology, 2021)
The discrepancy between natural sleep-wake rhythm and actual sleep times in shift workers can cause sleep loss and negative daytime consequences. Irregular shift schedules are particularly harmful and seem to increase the risk for insomnia. The present study compares insomnia symptoms of non-shift workers, regular shift workers and irregular shift workers and takes into account the moderating role of the Big Five personality traits and levels of perfectionism. Employees of an Austrian railway company completed an online survey assessing shift schedules, sleep quality and duration, daytime sleepiness, and personality traits. 305 participants, of whom 111 were non-shift workers, 60 regular shift workers, and 134 irregular shift workers made up the final sample. Irregular shift workers achieved significantly worse scores than one or both of the other groups in time in bed, total sleep time, sleep efficiency, sleep duration, sleep quality, sleep latency, and the number of awakenings. Nevertheless, one cannot speak of clinical insomnia, since the values achieved are still within average range. Participants working regular shifts reported the best sleep quality and longest sleep duration and showed the least nocturnal awakenings, possibly due to higher conscientiousness- and lower neuroticism-scores in this group. Agreeableness increased the effect of work schedule on total sleep time while decreasing its effect on the amount of sleep medication taken. Perfectionism increased the effect of work schedule on time in bed and total sleep time. Generalization of results is limited due to the high percentage of males in the sample and using self-report measures only.